Microenterprise Lending and Assistance Program (MELA): new product development - Haji, Raheem (© BRAC, 2016)
1. Current products and trend analysis 2. Inventory supply loan 3. Agricultural loans 4. Manufacturing loan 5. Parallel loan 6. Conclusion.